(1054) Surplus Labour and The Problem of Disguised Unemployment in the Egyptian Agriculture العمالة الفائضة ومشكلة البطالة المقنعة في الزراعة المصرية - Mohamed Nazem Hanafi. (INP, 2024)
The study addressed the concept of disguised unemployment and its various types, focusing on the Egyptian case. It included an empirical analysis to identify factors affecting disguised unemployment in the agricultural sector. In the first round of analysis, the impact of seasonal changes on disguised unemployment was examined, revealing that agricultural seasons significantly influence unproductive employment. In the second round, the study focused on the effects of farm size, household size, and seasonality on disguised unemployment. The findings showed that larger households and smaller farms increase the likelihood of excess labor, thereby exacerbating disguised unemployment. The study concluded with recommendations for policies to enhance productive efficiency and ensure fair resource distribution